2017
DOI: 10.1177/0046958017707296
|View full text |Cite
|
Sign up to set email alerts
|

Developing High-Functioning Teams: Factors Associated With Operating as a “Real Team” and Implications for Patient-Centered Medical Home Development

Abstract: Team-based care is a foundation of health care redesign models like the patient-centered medical home (PCMH). Yet few practices rigorously examine how the implementation of PCMH relates to teamwork. We identified factors associated with the perception of a practice operating as a real team. An online workforce survey was conducted with all staff of 12 primary care sites of Cambridge Health Alliance at different stages of PCMH transformation. Bivariate and multivariate analyses of factors associated with teamwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…At the system‐level, GeriPACTs reported leadership challenges such as perceived support for team objectives, stable team membership with minimal sharing, and co‐location of team members. Study of PACTs showed how leadership support limits the ability to build high‐functioning teams 3,5,10,11,14 . GeriPACTs described leadership support as limiting the ability of the team to provide geriatrics care by putting staffing, scheduling, and space needs in the context of patient characteristics, such as clinical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…At the system‐level, GeriPACTs reported leadership challenges such as perceived support for team objectives, stable team membership with minimal sharing, and co‐location of team members. Study of PACTs showed how leadership support limits the ability to build high‐functioning teams 3,5,10,11,14 . GeriPACTs described leadership support as limiting the ability of the team to provide geriatrics care by putting staffing, scheduling, and space needs in the context of patient characteristics, such as clinical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…We were also not surprised to see the strong association of practice leadership with TE. Within the practice transformation literature, more effective leadership has been associated with greater engagement of practice teams in change activities [ 37 ]. In an editorial, Bohmer outlines key physician leadership activities critical to organizational change, including leadership responsibilities with 1) defining care goals, 2) ensuring that “clinical microsystems” can execute such goals, 3) engaging in data driven QI methods, and 4) modeling how to step beyond usual boundaries in order to drive organizations towards “relentless” improvement [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because individual PACT members often report to different leaders within the clinic, PACT members rely upon local healthcare leadership to assist with resolution of within-team conflict resultion [ 5 ]. Notably, leadership support of the PACT model has been associated with: better recruitment and retention of PACT members [ 1 ]; stronger PACT teamwork [ 6 ]; greater sense of team member accountability to the PACT [ 5 ]; and better patient-reported access to care [ 7 ].…”
Section: Introductionmentioning
confidence: 99%